Comparing test methods for the mechanical characterization of fiber reinforced concrete. (11th October 2017) - Conforti, Antonio; Minelli, Fausto; Plizzari, Giovanni A.; Tiberti, Giuseppe
Abstract : Different tests are proposed by international standards for the evaluation of the mechanical properties of fiber reinforced concrete (FRC); among them, either beams or round determinate panels are generally used. However, different tests are accepted by design codes if reliable correlation factors between standard parameters are provided ( fib Model Code 2010). Within this context, a broad experimental program on both beams and round determinate panels was carried out in order to provide a critical discussion on material characterization and to evaluate possible correlation factors. Beam tests according to European (EN 14651), American (ASTM 1609), and Japanese (JCI‐SF4) standard, as well as small round panels and large round panels (according to ASTM 1550) were studied within an experimental program comprising 189 beams and 90 round panels. Unlike previous researches, mainly focused on steel fibers, two types of macro‐synthetic fibers were considered. Based on these experimental results, a comparison between test methods is presented, along with correlation approaches are proposed and critically discussed.